AESTHETIC VALUE IN ENGLISH, UZBEK AND TAJIK NATIONAL CULTURES (ResearchJet Journal of Analysis and Inventions, 2021)
Language plays indispensable role in understanding world picture of every nation. However, the problem of analyzing the expression of the concept of "beauty" in the language (in the English, Uzbek and Tajik national cultures) has not been studied from the point of view of cognitive linguistics and linguistic Culturology. Consequently, the aesthetic picture of the world in English, Uzbek and Tajik languages, the possibility of expressing and reflecting the concept of "beauty" on the phraseological and lexical tiers of the language, the interpretation of values in different cultures, comparative analysis of linguistic and cultural features, and the study in direct connection with cognitive linguistics, linguoculturology, general linguistics determine the relevance of the topic of the article.